W jaki sposób forma muzyczna staje się gatunkiem literackim - Piaskowski, Łukasz (Zagadnienia Rodzajów Literackich, 2023)
The aim of the article is to look at the problem of complicated relationships between musical forms and literary genres, as well as the process of transformation of one form into another. The main thesis of the text is the observation that musical forms affect literary works in two basic ways: they affect either the meaning (semantic integration) or the form (structural and compositional integration) of works. These processes can be accompanied by various creative motivations: transformational (intersemiotic translation, literary score) or metaformal (formal mimicry, metaform). The result of these operations is either works that translate the structure of a musical form into a poetic work, or works that merely imitate these forms, using musical motifs more freely. Separately, it is also worth distinguishing such a thematization of musical forms that leads to their use as a color metaphor or an object of description. An important problem raised in the article is also the issue of including musical poetic genres in the logic of the historical-literary process and considering them as forms undergoing development. A scherzo, a prelude or a nocturne written by representatives of positivist, modernist or interwar period literature should be considered in a completely different way. Musical literary forms were brought to life in the mid-nineteenth century, and over the next decades they were subject to historical, social, and cultural changes. Undoubtedly, cultural and ideological factors, and not only formal and compositional factors, contributed to their creation. Musical genres in poetry develop slightly differently for this reason, and their genesis allows for broadening the context enabling their proper interpretation.